Bio-Diesel as an Alternative Fuel for Compression Ignition Engine: A Review - Dr. Supriya Chavan, Mr. Shidagonda Jabade, Dr. M. Sakthivel (International Journal of Advanced Science and Technology, 2020)
Compression ignition (CI) engines are most commonly used in automobile sectors and power generation sector than spark ignition (SI) engines due to its fuel lean operation. The most common fuel source for diesel is petroleum based fossil fuel and it is depleting continuously at very faster rate. Many countries import the fossil fuel due to very low fossil fuel reserves; it directly impacts on economy of the countries. In addition to this, main problem associated with the CI engines are emissions like smoke, oxides of nitrogen (NOx) and carbon monoxide (CO). Since last many years researchers doing investigations to replace the fossil diesel fuel to several alternative fuels such as alcohols, dimethyl ether and biodiesel. Many number of investigations have been performed by number of researchers to check the suitability of biodiesel as an alternate fuel for CI engine and found that biodiesel is relevant alternative fuel for CI engines, due to characteristics like renewable, biodegradable, oxygen content, free from sulphur, also having certain advantages like low exhaust emissions, low wear and tear of engine, and low consumption of engine oil, hence researchers in all over world getting attention towards biodiesel. This paper presents the review of combustion, performance and exhaust pollutants from CI engine when biodiesel is used as a fuel.